Cyclopropyl‐tryptamine Analogues: Synthesis and Biological Evaluation as 5‐HT6 Receptor Ligands. Issue 1 (5th November 2012) - Szalata, Claude; Szymoniak, Jan; Fabis, Frédéric; Butt‐Gueulle, Sabrina; Rault, Sylvain; Bertus, Philippe; Gérard, Stéphane; Sapi, Janos
<x xml:space="preserve">Abstract</x> Conformational restrictions: Based on the pharmacophore model for 5‐HT6 receptor ligands (shown), tryptamine analogues bearing a cyclopropyl ring on the α‐position of the tryptamine side chain were synthesized and evaluated against 5‐HT receptors. N, N‐Dimethyl‐1‐arylsulfonyltryptamine derivatives exhibited promising selectivity for 5‐HT6 over 5‐HT1a and 5‐HT4 receptors and interesting activity against 5‐HT6 (Ki=∼0.15 μM; IC50=∼0.20 μM).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>